How Reliable is the Cuprates System to Recent Technology? - Emetere M.E.; Awojoyogbe O.B.; Uno U.E.; Isah K.U.; Sanni E.S.; Akinyemi M.L. (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The emergence of cuprates as a high Tc superconductor gave high hopes in the discovery of a room temperature superconductor. It is almost three decades and the highest critical temperature attained on the cuprates is about 135K. A brief overview was conducted on the progress made so far on the cuprates. A mathematical approach was used to design a formula which could determine the experimental results of critical temperature of versed cuprates superconductors. The result of our findings shows that the possibility of attaining the experimental room temperature cuprates superconductor seems very narrow. The study recommended an elaborate approach on the hybridization of cuprates for future research. Hence, there is possibility of having cuprates with wide engineering application.